JIGSAW WITH CROSSWORD-PUZZLE GAME IN IMPROVING STUDENTS' MASTERY OF ACCOUNTING VOCABULARY : A Mixed-Method Study at a Vocational High School in West Java - Wini Fitrina Sofyan, - (2018)
Mastery of accounting vocabulary is important for students of vocational high school. Nevertheless, the current curriculum only provides general English vocabulary which does not support students' accounting vocabulary mastery, so that students can hardly meet workplace requirements. Picking the materials of accounting vocabulary from ESP (English for Special Purposes), this study attempts to implement the accounting vocabulary teaching through the technique of Jigsaw with crossword-puzzle game. This research is a mixed method research: (a) qualitative: open-ended questionnaire, observation and semi-structured interview, and (b) quantitative: quasi-experimental design with pre-test and post-test. The participants are the second grade students in a vocational high school in West Java. They are divided into two classes as the control (24 participants) and experiment class (25 participants). The findings indicate that the implementation of this technique was effective in developing the students' mastery of accounting vocabulary. The analysis result of t-test shows that t-observed is higher than t-critic, (3,71 ˃ 2,02). It shows that jigsaw with crossword-puzzle game is an effective medium for increasing the students' mastery of accounting vocabulary since the elements of jigsaw and crossword-puzzle game facilitated an effective learning. Having positive attitudes, students believe that this implementation has enhanced their understanding the vocabulary found in accounting literatures, so that they have a good mastery of accounting vocabulary. Keyword: Accounting vocabulary, jigsaw, crossword-puzzle game Menguasai "kosakata akuntansi bahasa Inggris" sangat penting untuk siswa SMK program studi akuntansi. Namun, kurikulum yang ada belum memadai dengan hanya menyajikan "kosakata bahasa Inggris umum". Sehingga para siswa sulit memenuhi persyaratan kerja. Dengan mengambil materi kosakata akuntansi dari ESP (English for Special Purposes), studi ini mencoba mengenalkan kosakata akuntansi bahasa Inggris melalui teknik "Jigsaw dengan permainan teka-teki silang". Penelitian ini menggunakan metode penelitian gabungan dengan pengumpulan data: (a) kualitatif: angket skala Likert, observasi dan wawancara semi-terstruktur. (b) Kuantitatif: quasi-expermental dengan menggunakan desain pre-test dan post-test. Sampel penelitian ini menyertakan dua kelas pada program akuntansi kelas XI SMK di Jawa Barat. Mereka dibagi menjadi dua kelompok yaitu kelas kontrol (24 peserta) dan kelas eksperimen (25 peserta). Hasil penelitian mengindikasikan bahwa pengimplementasian Jigsaw dengan permainan teka-teki silang efektif dalam meningkatkan penguasaan kosakata akuntansi bahasa Inggris siswa. Hasil analisis dari rumus t-test juga menunjukan bahwa t-observasi lebih tinggi dari t-kritik, (3,71 ˃ 2,02). Hal ini mengindikasikan bahwa Jigsaw dengan permainan teka-teki silang adalah medium yang efektif untuk meningkatkan kemampuan siswa dalam penguasaan kosakata akuntansi bahasa Inggris. Semua elemen pada Jigsaw dan permainan teka-teki silang mampu memfasilitasi pembelajaran yang efektif. Serta siswa memiliki positive attitudes, juga siswa percaya bahwa pengimplementasian pembelajaran ini mampu meningkakan pemahaman kosakata akuntansi bahasa Inggris dalam berbagai literatur akuntansi. Kata kunci: Kosakata akuntansi, jigsaw, permainan teka-teki silang